Management of clinically lymph node-positive malignant pleural mesothelioma - Verma, Vivek; Wegener, Rodney E.; Adeberg, Sebastian; Horne, Zachary D.; Grover, Surbhi; Friedberg, Scott; Simone, Charles B. (Seminars in thoracic and cardiovascular surgery, 2010)
Nodal involvement in malignant pleural mesothelioma (MPM) is a poor prognostic factor, and management remains highly debated. Because there are no prospective trials for this population, this investigation addressed a major knowledge gap by examining national practice patterns as well as survival outcomes. The National Cancer Database was queried for newly diagnosed cN1-3M0 MPM. Multivariable logistic regression ascertained factors associated with administering surgery. Kaplan-Meier analysis assessed overall survival (OS); multivariable Cox proportional hazards modeling examined factors associated with OS. No statistical intergroup comparisons were made herein. This was primarily owing to undeniable selection biases in these heterogeneous datasets; the presence of incomplete and inadequately granular clinical information (eg, intent and selection of treatment, preoperative assessment) cannot be accounted for by propensity matching or other such algorithms, thus potentially leading to misinterpretation. Of 2548 patients, 20%, 70%, and 9% had N1, N2, and N3 disease, respectively. Overall, 13% received surgery/chemotherapy, 47% underwent chemotherapy alone, 30% were observed, and 5% received resection without chemotherapy (5% had unknown treatment information). The median OS for all patients was 9.2 months. Relative to N1 cases, N2+ subjects were less likely to undergo resection, and they also experienced lower OS (P < 0.05 for both). The median OS in N1, N2, and N3 patients was 10.0, 9.1, and 8.5 months, respectively. In summary, nodal status is a prognostic factor in cN+ MPM. Expected outcomes for the overall population and by nodal classification are described, which should be considered when patients and multidisciplinary providers jointly weigh management options. Careful patient selection in this population is necessary, encompassing factors such as histology, age, performance status, and location(s) of nodal burden.
Available online 19 June 2019
Gesehen am 20.04.2020